Turbidity factor coefficient on the estimation of hourly solar radiation in Depok City, Indonesia - Muhammad Arif Budiyanto; Nasruddin; M. Hanafi Lubis (Energy Reports, 2020)
Indonesia is a country located on the equator and is a tropical country that has two climates namely rainy and sunny. Indonesia has a long solar radiation intensity time that started from 8 AM until 16 PM, which the effective time is along 5 h on peak solar time. The calculation of solar radiation intensity is needed to know the efficiency power applicable to solar power technology. This paper will discuss the estimation of hourly solar radiation compared with measured data in the Department of Mechanical Engineering Universitas Indonesia, Depok City, Jawa Barat Province, Indonesia. The estimation of hourly solar radiation is based on Liu and Jordan's empirical models. The comparison of empirical model with measured data in order to know the influence of solar radiation parameters like turbidity factor coefficients and climate conditions used to calculate the solar radiation at the studied site. The turbidity factor coefficient assumed as a normal sky condition with the value is 0.88 and 0.26, respectively for A and B. These values were chosen based on the cloud cover data from the measurement that show there is no cloud cover during the day.
Keywords: 330; Solar radiation model; Hourly solar radiation; Turbidity factor